How Does Job Demands and Job Resources Affect Work Engagement Towards Burnout? The Case of Penang Preschool - Ahmad, Juliana; Fairos Saffardin, Siti; Ban Teoh, Kok (International Journal of Psychosocial Rehabilitation, 2020)
In recent years, preschool educators have been engaged with demanding quality teaching and complex administrative work in their environment. The excessive job demands and the insufficient job resources have resulted in preschool educators encountering greater burnout and influencing their work engagement. Hence, the paper aims to investigate the predictors of burnout among preschool educators as well as the potential mediating role of work engagement. This study proposes that job demands have a significant positive relationship with burnout, while job resources and work engagement have a significant negative relationship with burnout. In addition, work engagement is demonstrated to possess a significant mediator between job resource and burnout. Therefore, this study is priceless to both scholars and practitioners who wish to monitor and decrease the burnout prevalence among preschool educators.